2010
DOI: 10.1002/biot.201000048
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance at the crossroads of metabolic syndrome: Systemic analysis using microarrays

Abstract: Recently, it has been suggested that insulin resistance is a better predictor of metabolic syndrome than obesity. Numerous studies have been conducted to identify insulin resistance susceptibility genes in various model systems. This review focuses on recent findings in microarray analyses, which have indicated that (i) in the liver, genes involved in lipid synthesis and gluconeogenesis are increased in an animal model of insulin resistance that leads into liver steatosis and hyperglycemia; (ii) in adipose tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Some genetic work has recently shown promise. Although far from clinical use, microarray analysis of genes in muscle, adipose tissue and the liver shows alterations in the setting of IR [62] . Serum genetic markers may lead to future genetic techniques to detect and monitor IR.…”
Section: Assessment Of Insulin Resistancementioning
confidence: 99%
“…Some genetic work has recently shown promise. Although far from clinical use, microarray analysis of genes in muscle, adipose tissue and the liver shows alterations in the setting of IR [62] . Serum genetic markers may lead to future genetic techniques to detect and monitor IR.…”
Section: Assessment Of Insulin Resistancementioning
confidence: 99%
“…Most of these studies have focused on identifying the transcriptional changes underlying the pathophysiology of obesity, as well as the anti-obesity effects of dietary, pharmacological, and behavioral interventions (Sun 2007). In a consequence, thousands of genes differentially expressed between lean and obese individuals have been identified, including those related to the hepatic glucose and lipid metabolism, insulin signaling, inflammation, coagulation, cell adhesion, oxygen stress, and activity of chaperone (Sharma et al 2006; Greco et al 2008; Kim 2010; Naik et al 2013). On the contrary, a limited number of muscle transcriptomic studies have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In one series of them, a short-term feeding of mice with HFD changed the expression of more than 1,000 genes in the skeletal muscle (de Wilde et al 2008), but an 8-week HFD feeding induced rather small alterations in the muscle transcriptome, with up-regulation of only Fatty acid oxidation pathway (de Wilde et al 2009). Others studies revealed, however, that overall gene expression in muscle, involved in fatty acid oxidation and biosynthesis, was either decreased or obesity unresponsive (Kim 2010). …”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary research effort involving a combination of clinical, biochemical and omics approaches appears mandatory to increase knowledge in the complexity of biological traits and processes associated with obesity [5]. Through probing of the transcriptional activity of tissues, the techniques allowing systematic analysis of AT gene expression have proved useful at identifying master genes [6] and regulatory networks involved in human obesity and related disorders [7]. Moreover, mRNAs are molecular species easily and evenly amplified.…”
Section: Introductionmentioning
confidence: 99%